Rapid and scalable personalized ASO screening in patient-derived organoids - John C. Means; Anabel L. Martinez-Bengochea; Daniel A. Louiselle; Jacqelyn M. Nemechek; John M. Perry; Emily G. Farrow; Tomi Pastinen; Scott T. Younger (Nature, 2025)
Abstract Personalized antisense oligonucleotides (ASOs) have achieved positive results in the treatment of rare genetic disease1. As clinical sequencing technologies continue to advance, the ability to identify patients with rare disease harbouring pathogenic genetic variants amenable to this therapeutic strategy will probably improve. Here we describe a scalable platform for generating patient-derived cellular models and demonstrate that these personalized models can be used for preclinical evaluation of patient-specific ASOs. We describe protocols for delivery of ASOs to patient-derived organoid models and confirm reversal of disease-associated phenotypes in cardiac organoids derived from a patient with Duchenne muscular dystrophy (DMD) with a structural deletion in the gene encoding dystrophin (DMD) that is amenable to treatment with existing ASO therapeutics. Furthermore, we designed novel patient-specific ASOs for two additional patients with DMD (siblings) with a deep intronic variant in the DMD gene that gives rise to a novel splice acceptor site, incorporation of a cryptic exon and premature transcript termination. We showed that treatment of patient-derived cardiac organoids with patient-specific ASOs results in restoration of DMD expression and reversal of disease-associated phenotypes. The approach outlined here provides the foundation for an expedited path towards the design and preclinical evaluation of personalized ASO therapeutics for a broad range of rare diseases.